2021
DOI: 10.1051/e3sconf/202131901052
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant and antimicrobial activities of the essential oil of Illicium verum

Abstract: In recent years, a concern has been expressed about the impact of antibiotics and synthetic antioxidants, which are used to inhibit microbial growth and retard fat oxidation in foods. In addition, antibiotic resistance presents a serious menace to human and environmental ecosystems. This has led the food industry to use natural resources such as essential oils in the preparation of foods, this forming their sensory profile and increasing preservation time there. The objective of this work is to determine the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…As for star anise EO, its yield was 4.01 ± 0.08% v / w . This percentage yield was similar to those reported in many studies, such as 4.0% v / w [ 16 ], 4.0–4.5% v / w [ 40 ], and 4.13% v / w [ 41 ], but it differed considerably from the EO yield result reported by Soonwera et al [ 42 ] at 9.6% v / w. The EO chemical analysis from the GC–MS of lemongrass and star anise revealed that their chemical compositions matched those previously reported [ 16 , 19 , 42 , 43 ]. Geranial was revealed to be the main constituent of lemongrass EO, accounting for 46.83 ± 1.02% of the total chemical composition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for star anise EO, its yield was 4.01 ± 0.08% v / w . This percentage yield was similar to those reported in many studies, such as 4.0% v / w [ 16 ], 4.0–4.5% v / w [ 40 ], and 4.13% v / w [ 41 ], but it differed considerably from the EO yield result reported by Soonwera et al [ 42 ] at 9.6% v / w. The EO chemical analysis from the GC–MS of lemongrass and star anise revealed that their chemical compositions matched those previously reported [ 16 , 19 , 42 , 43 ]. Geranial was revealed to be the main constituent of lemongrass EO, accounting for 46.83 ± 1.02% of the total chemical composition.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in good agreement with previous results [16,42] indicating that the trans-anethole percentage in the chemical composition was 93.58-94.0%. The findings from some other studies were slightly different: 80.0% [48], 81.04% [40], and 83.46% [41]. The difference in the EO yield and the chemical composition of lemongrass and star anise EOs were affected by many factors, such as plant genotype, plant age, maturity stage, harvesting stage, primary developmental period, quality of raw plant materials, and good management practice of cultivation [49][50][51].…”
Section: Discussionmentioning
confidence: 79%
“…The study's results not only confirmed the heightened efficacy of IVEO against G + strains but also demonstrated its potent antibacterial activity against each MDR clinical isolate tested [44]. In an independent investigation, the antibacterial properties of this essential oil were evaluated against six distinct pathogens, of which Staphylococcus aureus was the most susceptible, followed by Staphylococcus epidermidis and Enterobacter cloacae [45]. Additionally, it was noted that essential oils made from star anise were inactive against Salmonella typhi but had a potent activity against S. aureus and E. coli [46].…”
Section: Discussionmentioning
confidence: 52%
“…In recent years, the impact of antibiotics, which are used to inhibit microbial growth and slow fat oxidation in food, has been observed [3]. This has led the food industry to use natural resources such as essential oils in the preparation of foods [4]. This fact has generated a renewed interest in plant therapy medicine in recent decades [5].…”
Section: Introductionmentioning
confidence: 99%